2014
DOI: 10.1007/s00038-014-0640-0
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and disability: differences between generations of Canadian immigrants

Abstract: First-generation immigrants were less likely to be disabled than the other generations. Education, employment and income provide important avenues through which individuals develop health literacy. Health literacy was not associated with disability among first-generation immigrants perhaps because health literacy is low in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…First-generation immigrants are less likely to report disability, as compared to the third generation [45]. Yet no significant difference in disability reporting was found between the second-and the thirdplus generations.…”
Section: Cultural Change Between Generations: Coping With Cultural Chmentioning
confidence: 72%
See 1 more Smart Citation
“…First-generation immigrants are less likely to report disability, as compared to the third generation [45]. Yet no significant difference in disability reporting was found between the second-and the thirdplus generations.…”
Section: Cultural Change Between Generations: Coping With Cultural Chmentioning
confidence: 72%
“…Health literacy was found to be significantly negatively associated with disability reporting only of the first-generation immigrants. This may be due to the low functional health literacy among first-generation immigrants, while better education, employment and higher income in the new country, providing paths for the second-and third-plus generations to develop better health literacy competencies for accessing and navigating the health system [45]. Some programs have even targeted young immigrants, as a means to improve access to care for entire migrant families.…”
Section: Cultural Change Between Generations: Coping With Cultural Chmentioning
confidence: 99%
“…Even though health literacy was significantly associated with good self-rated health, discordance between native language and language of data collection reduced the effect of health literacy to non-significance. Similarly, another study from Canada found that among different generations of immigrants, health literacy was significantly associated with reported disability but the effect was largely accounted for by differences in education, employment and income [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A small number of articles outline how Nutbeam’s (2008) levels of health literacy are relevant to former refugee populations settling in high-income countries such as Australia, Norway, Canada, and Sweden (Gele, Pettersen, Torheim & Kumar, 2016; Geltman et al, 2013; Khuu, Lee, Zhou, Shin & Lee, 2016; Omariba, & Ng, 2015; Wangdahl, Lytsy, Martensson, & Westerling, 2014). It has been noted by some authors that interactive and critical health literacy may work differently among former refugee communities where literacy problems are compounded by unfamiliarity with the health system (Gele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%